Pemberdayaan Kader Kesehatan Desa Sempalwadak Kec. Bululawang, Kab. Malang melalui Pengolahan Daun Mint Menjadi Sediaan Teh Sebagai Relaksan pada Lansia - Sirilus Deodatus Sawu; Venny Kurnia Andika (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Mint (Mentha piperita) leaves contain menthol and volatile compounds that provide relaxing and cooling effects and may improve comfort and sleep quality. These properties offer a non-pharmacological alternative for reducing sleep disturbances, anxiety, and stress among older adults. Sempalwadak Village, Bululawang District, has abundant mint resources; however, their utilization remains limited. This community service program aimed to empower community health cadres through training on the hygienic and safe processing of mint leaves into herbal tea for older adults. Seventeen health cadres participated in educational sessions and hands-on training. Program effectiveness was evaluated using pre-test and post-test assessments to measure knowledge improvement and observational checklists to assess practical skills. Success was defined as a minimum 30% increase in knowledge scores and good practical skills. The results showed a 47.43% increase in mean knowledge scores, while the average skill score reached 3.80, categorized as very good. The program effectively improved cadres’ knowledge and skills in utilizing local herbal resources to support health promotion and disease prevention for older adults.